Infrarenal Abdominal Aortic Pseudoaneurysm with Suspected Behcet Disease: A Unique Case Report - Gunardi, Harsya D; Pratama, Danny; Prabowo, Andrio W; Hidayat, Nanang W; Putera, M Aprizal; Krisandi, Grady (The New Ropanasuri Journal of Surgery, 2024)
Introduction. Abdominal aortic pseudoaneurysm caused by autoimmune vasculitis is a rare complication. Clinical presentation of patients is often late with life–threatening complications. Case Illustration: A 62–year–old male patient with infrarenal abdominal aortic pseudoaneurysm presenting with a 2–week worsening severe abdominal and lumbar pain with a history of uncontrolled hypertension and a history of oral ulcer. He was successfully treated with tube grafting through open surgical repair. Conclusion: The pseudoaneurysm was successfully removed and replaced with a polyester tube graft with no perioperative complications and was discharged 5 days later